2022
DOI: 10.3390/vaccines10020225
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Antibodies after BNT162b2 Vaccination Exhibit Reduced Binding against SARS-CoV-2 Variants of Concern

Abstract: SARS-CoV-2-specific antibody responses are engendered in human milk after BNT162b2 vaccination. However, the emergence of variants of concern (VOCs) raises concerns about the specificity of and potential cross-protection mediated by milk antibody responses, which are crucial for passive immunity transferred from breastfeeding mothers to their infants. In this study, we collected milk samples at three different time points pre- and post-vaccination, and measured milk IgA antibody binding to the receptor binding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Here, we demonstrated that the primary series of maternal mRNA vaccination elicited broad IgG and IgA antibodies that bound to all four variant strains included in this analysis (Alpha, Beta, Delta, Gamma) in both serum and breast milk. Low et al similarly reported breast milk IgA antibodies against RBDs across these four variants of concern, though with significant reductions for Beta, Delta, and Gamma [28]. Though our study and others have noted significant variances in the response to some variants of concern, these results indicate that maternal vaccination with a primary mRNA series generally elicits cross-reactive antibodies to multiple SARS-CoV-2 variants that are secreted into the breast milk and passively transferred to the infant.…”
Section: Discussionsupporting
confidence: 43%
“…Here, we demonstrated that the primary series of maternal mRNA vaccination elicited broad IgG and IgA antibodies that bound to all four variant strains included in this analysis (Alpha, Beta, Delta, Gamma) in both serum and breast milk. Low et al similarly reported breast milk IgA antibodies against RBDs across these four variants of concern, though with significant reductions for Beta, Delta, and Gamma [28]. Though our study and others have noted significant variances in the response to some variants of concern, these results indicate that maternal vaccination with a primary mRNA series generally elicits cross-reactive antibodies to multiple SARS-CoV-2 variants that are secreted into the breast milk and passively transferred to the infant.…”
Section: Discussionsupporting
confidence: 43%
“…In other relevant studies, no significant difference in IgG titers was observed between 30 and 60 days post vaccination [57,80]. Even IgG levels wane over time, but remain in detectable levels 2 [57], 3 [38,53,72] and 6 months post vaccination [49,73]. Contrarily with total IgG levels, secretory IgG antibodies continuously increase even 6 months after the first dose of mRNA vaccines [54].…”
Section: Anti-sars-cov-2 Igg Immunoglobulinsmentioning
confidence: 79%
“…Vaccination of pregnant women against COVID-19 is also beneficial for their children, as it reduces the risk of hospitalization due to COVID-19 before 6 months of age and the severity of the disease [20]. Regarding vaccination during breastfeeding, the breast milk of vaccinated individuals has been shown to contain antibodies and T cells specific for SARS-CoV-2, which may contribute to the development of the breastfed child's immune system [21,22].…”
Section: а к т у а л ь н і т е м иmentioning
confidence: 99%